Elimination of Interferences in the Determination of Palladium, Platinum and Rhodium Mass Fractions in Moss Samples using ICP‐MS/MS. Issue 4 (26th April 2016) - Suoranta, Terhi; Bokhari, Syed N. H.; Meisel, Thomas; Niemelä, Matti; Perämäki, Paavo
Abstract : Moss samples ( Pleurozium schreberi ) exposed to traffic‐related emission of Pd, Pt and Rh were analysed in this study. Successful elimination of interferences was achieved in the determination of Pd, Pt and Rh mass fractions in these samples using inductively coupled plasma‐tandem mass spectrometry (ICP‐MS/MS). Based on the results, a reliable determination of Pd, Pt and Rh mass fractions in microwave‐digested moss samples was obtained using ammonia (10% NH3 in He) in the collision/reaction cell when 103 Rh was measured either on‐mass (103→103) or with mass‐shift (103→171) and mass‐shifts for 108 Pd (108→159) and 195 Pt (195→229) were used. The ICP‐MS/MS procedure was validated using BCR‐723 (road dust) as a reference material. In addition, a good agreement between the ICP‐MS/MS results and the results obtained with cloud point extraction and quadrupole ICP‐MS was observed for the moss samples. Key Points: Mass fractions of Pd, Pt and Rh in moss samples were successfully determined using the ICP‐MS/MS technique. Effective interference removal was obtained using ammonia as a reaction gas. The measurement procedure was validated with cloud point extraction ICP‐QMS and with certified reference material BCR‐723.